(untitled) (AL MUNAZHZHARAH, 2023)
Waqf plays a crucial role in the social life of muslim society, so clerics set the elements and conditions on the administrations of waqf. Whereas indonesi’as representatives have been organized through a long proces. The research formulated on the system that was adopted by the waqf deed officer and the role of the head of the religious affairs office as the waqf ow officer in setting the waqf issue. To analyze the role of the head of the religious affairs office as the acting officer of the waqf ow in order to prevent the waqf isue from taking place. The kind of reseach used was the kind of fieldresearch, it,s meant to be a systematic investigation of on-site data. With a qualitative approach to understanding the phenomenan of what the research subject experiences about the role of the head of the religious affairs office as the acting officr of the waqf vow. This research data is generated through interviews. Further analysis will take place through the three stateges : Data Reduction, Data Presentation, Data Verification. This study as shown that, obstacles in various shape, some still knock, some time, fasum like housing. If the situation isa problem, then it will be difficult for us to solve the problem. To avoid and prevent future disputes or problems. So the waqf deed officer called the waqf, nazhir and the people who wanted to protect the land, to come to the religious affairs office to register the land, the way to encourage people who wish to address the villages. The deed to waqf vow is next. With the loan of waqf deed and the land deed of the waqf offiial making of the waqf, it is younger to present and present evidence of a future land dispute. The role of the head of the religious affairs office as the acting officer of the waqf was to be effective on the basis of the people’s image, including that there was no charge for the liquidity of the land. Not because there was already an indonesian body of waqf under the kediri KH. Zubaiduzzaman.